Probing human heart TCA cycle metabolism and response to glucose load using hyperpolarized [2‐13C]pyruvate MRS - Chen, Hsin‐Yu; Gordon, Jeremy W.; Dwork, Nicholas; Chung, Brian T.; Riselli, Andrew; Sivalokanathan, Sanjay; Bok, Robert A.; Slater, James B.; Vigneron, Daniel B.; Abraham, M. Roselle; Larson, Peder E. Z. (NMR in biomedicine, 2024)
Introduction The healthy heart has remarkable metabolic flexibility that permits rapid switching between mitochondrial glucose oxidation and fatty acid oxidation to generate ATP. Loss of metabolic flexibility has been implicated in the genesis of contractile dysfunction seen in cardiomyopathy. Metabolic flexibility has been imaged in experimental models, using hyperpolarized (HP) [2‐13C]pyruvate MRI, which enables interrogation of metabolites that reflect tricarboxylic acid (TCA) cycle flux in cardiac myocytes. This study aimed to develop methods, demonstrate feasibility for [2‐13C]pyruvate MRI in the human heart for the first time, and assess cardiac metabolic flexibility. Methods Good manufacturing practice [2‐13C]pyruvic acid was polarized in a 5 T polarizer for 2.5–3 h. Following dissolution, quality control parameters of HP pyruvate met all safety and sterility criteria for pharmacy release, prior to administration to study subjects. Three healthy subjects each received two HP injections and MR scans, first under fasting conditions, followed by oral glucose load. A 5 cm axial slab‐selective spectroscopy approach was prescribed over the left ventricle and acquired at 3 s intervals on a 3 T clinical MRI scanner. Results The study protocol, which included HP substrate injection, MR scanning, and oral glucose load, was performed safely without adverse events. Key downstream metabolites of [2‐13C]pyruvate metabolism in cardiac myocytes include the glycolytic derivative [2‐13C]lactate, TCA‐associated metabolite [5‐13C]glutamate, and [1‐13C]acetylcarnitine, catalyzed by carnitine acetyltransferase (CAT). After glucose load, 13C‐labeling of lactate, glutamate, and acetylcarnitine from 13C‐pyruvate increased by an average of 39.3%, 29.5%, and 114% respectively in the three subjects, which could result from increases in lactate dehydrogenase, pyruvate dehydrogenase, and CAT enzyme activity as well as TCA cycle flux (glucose oxidation). Conclusions HP [2‐13C]pyruvate imaging is safe and permits noninvasive assessment of TCA cycle intermediates and the acetyl buffer, acetylcarnitine, which is not possible using HP [1‐13C]pyruvate. Cardiac metabolite measurement in the fasting/fed states provides information on cardiac metabolic flexibility and the acetylcarnitine pool. Hyperpolarized [2‐13C]pyruvate was used to investigate metabolic flexibility in healthy human heart for the first time. In this first‐in‐human study, 13C‐label incorporation in the glycolytic derivative [2‐13C]lactate, TCA‐associated metabolite [5‐13C]glutamate, and [1‐13C]acetylcarnitine was assessed in the fasting and fed states in three healthy volunteers. Oral glucose load increased 13C‐labelled lactate, glutamate, and acetyl‐carnitine in all study subjects, reflecting metabolic flexibility.